Correction: Choi et al. Anti-Allergic and Anti-Inflammatory Effects of Undecane on Mast Cells and Keratinocytes. Molecules 2020, 25, 1554 - Dabin Choi; Wesuk Kang; Taesun Park (Molecules)
The authors would like to modify the Conflicts of Interest Section of the following published paper [...]